2012
DOI: 10.2147/copd.s32451
|View full text |Cite
|
Sign up to set email alerts
|

Once-daily NVA237 improves exercise tolerance from the first dose in patients with COPD: the GLOW3 trial

Abstract: IntroductionExercise limitation, dynamic hyperinflation, and exertional dyspnea are key features of symptomatic chronic obstructive pulmonary disease (COPD). We assessed the effects of glycopyrronium bromide (NVA237), a once-daily, long-acting muscarinic antagonist, on exercise tolerance in patients with moderate to severe COPD.MethodsPatients were randomized to a cross-over design of once-daily NVA237 50 μg or placebo for 3 weeks, with a 14-day washout. Exercise endurance, inspiratory capacity (IC) during exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
108
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(117 citation statements)
references
References 34 publications
(44 reference statements)
5
108
1
3
Order By: Relevance
“…In clinical trials, once-daily LABD have consistently improved not only airflow limitation, but also to a greater extent hyperinflation (as expressed by IC), both at rest and during exercise and these effects are translated into improvements in dyspnea and exercise capacity (18)(19)(20). Moreover, by deflating the lungs, bronchodilators effectively improve ventilatory muscle performance and lung mechanics, resulting in improvement of neuromechanical coupling, leading to alleviation of dyspnea (21).…”
mentioning
confidence: 99%
“…In clinical trials, once-daily LABD have consistently improved not only airflow limitation, but also to a greater extent hyperinflation (as expressed by IC), both at rest and during exercise and these effects are translated into improvements in dyspnea and exercise capacity (18)(19)(20). Moreover, by deflating the lungs, bronchodilators effectively improve ventilatory muscle performance and lung mechanics, resulting in improvement of neuromechanical coupling, leading to alleviation of dyspnea (21).…”
mentioning
confidence: 99%
“…86 The rate of AEs observed in short-duration clinical trials is about 5%, and not significantly different to placebo controls. 87,88 A series of GLOW trials has investigated the use of glycopyrronium in extended duration of up to 52 weeks, either as monotherapy or in combination with LABAs. Most studies have found low incidences of extra-pulmonary effects among subjects without significant cardiovascular co-morbidity.…”
Section: Glycopyrronium (Nva237)mentioning
confidence: 99%
“…Significant improvements have been observed with glycopyrronium versus placebo in lung function and clinical end-points, such as health status, dyspnoea, rescue medication use, daily symptoms, exercise endurance time and rate of exacerbations in three major clinical trials [23,[71][72][73].…”
Section: Glycopyrroniummentioning
confidence: 99%
“…Triple therapy (the combination of a LABA/LAMA with an ICS, or an ICS/LABA with a LAMA) is a treatment option for patients in GOLD group D. The improvements in lung function and clinical end-points observed with glycopyrronium [71][72][73][74] suggest that the LAMA may be a suitable candidate for use in a loose triple combination with an ICS/LABA. To study the efficacy of glycopyrronium in this approach, the GLISTEN trial investigated the efficacy (non-inferiority) of glycopyrronium compared with blinded tiotropium when added to twice-daily SFC [75].…”
Section: Glycopyrroniummentioning
confidence: 99%